THE ROLE OF STUDENTS’ MOTIVATION AS INNOVATION IN EDUCATION - Mirkhodjaeva Dilorom Batirovna (Journals Park Publishing, 2022)
The article considers role of students’ motivation in education process.
Keywords: motivation, education innovation, program, good teaching clear, goals and standards